Factors Influencing Parents’ Decisions in Choosing Early Childhood and Primary Education Institutions - Melva Herlina Sarma Uli Manalu; Ronald Suryaputra; Dany M. Handarini (Journal of Educational Management Research, 2026)
This study aims to analyze the influence of curriculum, facilities, location, and brand image on parents’ decisions to enroll their children at an integrated early childhood and primary education institution. Employing a quantitative approach with a survey design, data were collected from 55 parents of students in the 2025/2026 academic year selected from a population of 77 respondents. The data were obtained using a Likert-scale questionnaire and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine the relationships among variables. The results reveal that curriculum has a positive and significant effect on parents’ school choice decisions, indicating that curriculum relevance, quality, and future orientation play a crucial role in shaping parental preferences. In contrast, school facilities and location do not show a significant influence, suggesting that these factors are perceived as basic requirements rather than key differentiators in the school selection process. Furthermore, brand image has a positive and significant effect and emerges as the most dominant factor influencing parents’ decisions, as a strong school image fosters trust, reflects perceived educational quality, and enhances parental confidence. These findings imply that for newly established schools, the development of a strong and relevant curriculum supported by effective brand image management is essential to influence parents’ enrollment decisions, while facilities and location function primarily as supporting factors rather than main determinants.